(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
The vitality of yeast cells C. guilliermondii НП-4 and its change under the influece of X-rays was investigated. It has been shown that in radiated cells no vitality was observed, and after postradiated incubation the yeast vitality was реcovered partially, although in comparison with non-radiated cells it remained significantly low.